Vaping patterns, nicotine dependence and reasons for vaping among American Indian dual users of cigarettes and electronic cigarettes - Dorothy A. Rhoades; Ashley L. Comiford; Justin D. Dvorak; Kai Ding; Michelle Hopkins; Paul Spicer; Theodore L. Wagener; Mark P. Doescher (BMC, 2019)
Abstract Background The American Cancer Society discourages the dual use of electronic cigarettes (ECs) and cigarettes because such use has not resulted in reduced exposures to the harmful effects of smoking. American Indian (AI) people have the highest prevalence of smoking and of EC use in the United States, but very little is known about dual EC and cigarette use in AI communities. Methods In 2016, 375 adult AI in Oklahoma who smoked cigarettes completed a survey about EC use (vaping). We describe vaping patterns, nicotine dependence, and reasons for EC use among the subset of 44 (12%) current dual EC users. To differentiate habitual EC users from occasional or merely curious users, we defined dual use as using ECs on some days or every day in the past 30 days. Results About one-third of dual users vaped ten or more times daily. About two-thirds used a tank product. Eleven percent used ECs without nicotine and another 9% were unsure of the nicotine content. A minority (40%) enjoyed vaping more than smoking, and most (76%) would smoke first on days they did both. Thirty-one percent vaped within 5 min of waking and another 24% within 30 min. Although the two-item heaviness of use index did not differ significantly between smoking and vaping, the ten-item Penn State Dependence Index (PSDI) suggested greater dependence on smoking than vaping (11.02 vs. 6.42, respectively; p < .0001). The most common reasons for vaping were to reduce smoking (79%), enjoyment of flavors (78%), and ability to vape where smoking is not allowed (73%). Perceptions of less harm to others (69%) or to self were the next most common (65%). Fewer than half used ECs to reduce stress, for affordability, or because others used them. Conclusions Nearly 20% of dual users used ECs either without nicotine or without knowing if the product contained nicotine. The PSDI indicated greater dependence on smoking than vaping. Reasons for vaping were nearly equal between smoking reduction and enjoying flavors. Understanding patterns of dual use will inform future efforts to address nicotine dependence for AI communities with high prevalence of smoking.